Clinical spectrum of sarcoidosis in patients at a tertiary care hospital, Pakistan: 10-year follow-up study - Ainan Arshad; Mehmood Riaz; Zehra Naseem; Fatima Qadri; Syed Mujtaba Baqir; Muhammad Talal Ibrahim; Ahmed Ayaz (Journal of the Pakistan Medical Association, 2022)
Objectives: To identify the local patterns of manifestations, organ involvement other than lungs, diagnostic tools and treatment regimens related to patients of sarcoidosis. Method: The retrospective study was conducted from November 1, 2019, to February 28, 2020, at the Aga Khan University Hospital, Karachi, and comprised data of sarcoidosis patients who needed hospitalisation between 2009 and 2019. The entire clinical spectrum was noted based on organ involvement. Data was analysed using SPSS 21. Results: Of the 80 patients, 53(66.3%) were women. The overall mean age at diagnosis was 52.0+/-13.5 years. Pulmonary sarcoidosis was found in 60(75%) patients, while 13(16.3%) had extrapulmonary manifestations, and 6(8.8%) had both pulmonary and extrapulmonary involvement. None of the patient had hypercalcemia, while antinuclear antibodies was positive in 2 (18.2%) patients. In terms of treatment, 75(93.8%) patients received corticosteroids. Acute exacerbation of interstitial lung disease was the most common reason of hospitalisation 16(20%). Mortality was the outcome in 11(14.7%) cases. Conclusion: Sarcoidosis was found to be more prevalent in women aged 50 years and above. A quarter of patients had extrapulmonary manifestation, while interstitial lung disease was the most common complication. Key Words: Sarcoidosis, Pulmonary, Extrapulmonary, Clinical spectrum.